Case report: Paratesticular dedifferentiated liposarcoma with poor prognosis - Suto, Hirotaka; Inui, Yumiko; Okamura, Atsuo (Frontiers in Oncology, 2022)
Background/Aim: Most paratesticular liposarcomas (PLPSs) are well-differentiated liposarcomas (WDLPSs) with favourable prognoses. As such, the rare occurrence of PLPS often leads to its misdiagnosis as a hernia or hydrocele on physical examination. Curative resection of the tumour may not be possible in cases where PLPSs have transformed into dedifferentiated liposarcomas (DDLPSs) owing to a delay in diagnosis. Herein, we describe a case of unresectable paratesticular dedifferentiated liposarcoma (PDDLPS) with poor prognosis due to delayed diagnosis. Case Report: A 57-year-old man visited our hospital with a chief complaint of a right scrotal mass, which was diagnosed as scrotal hydrocele but without treatment or follow-up. Eight years later, the patient complained of abdominal distension, and a computed tomography scan revealed the presence of retroperitoneal and right scrotal masses. The right scrotal mass was removed, and histopathology revealed DDLPS. The patient was diagnosed with unresectable PDDLPS metastasising to the retroperitoneum, and the left pleura was treated with doxorubicin. After an initial response, pleural effusion and ascites increased during the sixth cycle of chemotherapy. The patient subsequently received eribulin but died 5 months after the initial DDLPS diagnosis. Conclusion: It is difficult to distinguish PLPS from benign inguinal hernia and hydrocele testis on physical examination. PLPS generally has a considerably good prognosis. However, failure to diagnose WDLPS can be dangerous as it might lead to malignant transformation to DDLPS, which has a poor prognosis. Physicians should consider this malignancy when examining patients with hernias or hydroceles of the inguinal region and should perform ultrasonography or magnetic resonance imaging.